Research on Conducted Disturbance to Secondary Cable Caused by Disconnector Switching Operation - Chen, Xiaoyue; He, Zeyu; Zhang, Yanze; Si, Junjie; Wang, Shuang; Wan, Baoquan; Liu, Jianben (Frontiers in Energy Research, 2022)
The disconnector switching operation in GIS not only generates very fast transient overvoltage (VFTO) in primary equipment, but also couples to the secondary system, which affects normal operation of the secondary equipment. In this study, aiming at the conducted disturbance caused by disconnector switching operation of the 1000 kV UHV GIS test circuit on the secondary cable, a broadband equivalent circuit model of the potential transformer and the grounding grid is proposed based on the vector fitting method and the impedance synthesis method, and the accuracy of the model is tested. On the basis of this model, the conducted disturbance voltage of the secondary cable core is obtained by combining the measured typical disturbance source waveform. The research results of the influencing factors of conducted disturbance show that the amplitude of the disturbance voltage generated by the capacitive conduction is higher than that generated by the resistive conduction, but the main frequency of the resistive conducted disturbance voltage is higher. The amplitude of the conducted disturbance voltage will decrease with the increase of the length of the cable and the length of the grounding wire. The single-ended grounding of the secondary cable shield at the GIS side will cause serious disturbance voltage. The research results of this study will be beneficial to the protection of secondary cable electromagnetic disturbance in intelligent substation, and have reference significance for the implementation of secondary equipment protection measures in intelligent substation.